Detection of HSP70 in Working Horses Using ELISA on Sumbawa Island - Haddar, Mariyam Al; Pradana, Munawer; Kholik, Kholik; Supriadi, Supriadi; Satuman, Satuman (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Heat shock protein 70 also known as HSP70 is a protein that regulates in response to stress factors such as heat, exercise, and others. The current research work used enzyme-linked immunosorbent assay (ELISA) to measure HSP70 levels in working horses on Sumbawa Island. Blood was taken through jugular venipuncture whereas saliva was collected non-invasively via cotton swab, both were analyzed with ELISA. The results indicated different expressions of HSP70; saliva shows a significantly higher level of HSP70 (52.07 Â± 25.25 ng/mL) than serum (43.71 Â± 34.83 ng/mL) from the same animal. The observed differences might indicate a better representation of acute stress by saliva due to physiological rapid turnover compared to serum, which reflects an integration of cumulative stress exposure. Our finding thus proves that double monitoring of both biological matrices offers complementary information in assessing stress in working horses while taking salivary HSP70 into account as especially promising for the in-field welfare monitoring due to its non-invasive collection and sensitivity to immediate stress conditions.